Perceptual Dynamics of Striving to Make Children with Hearing Impairment Speak in Education - Iline, Chingombe Shamiso; Simuforosa, Magwa (International Journal For Research In Educational Studies, 2018)
The study focused on participants’ views over striving to make children with hearing impairment speak in education. In Zimbabwe the official language of children with hearing impairment is sign language, while hearing individuals use an aural-auditory language. Some measures are being put in place to ensure that the hearing impaired child adopts the hearing culture. As a result, they are coerced to adopt both the hearing and the deaf cultures. A qualitative methodology was used through an interpretive research paradigm. A sample of 10 hearing impaired pupils, 5 teachers and 5 parents was purposively selected. Questionnaires and interviews were used to solicit data from the participants. Data were analysed using thematic data analysis. Mixed perceptions were highlighted by the research participants. Some participants argued that it was a noble idea to encourage the child with hearing impairment to speak. Their argument was that this will allow them to fit well in the larger community which is a hearing one. Other participants felt that coercing children with hearing impairment to talk is against the will of the Creator. The children with hearing impairment felt that this is creating some confusion. They indicated that they are quite comfortable in the Deaf culture. However, some expressed that they are eager to leave their marginal society. The researcher recommended that both cultures co-exist. Children with hearing impairment should be at liberty to use the language that they are comfortable with.